2020
DOI: 10.1590/fst.01219
|View full text |Cite
|
Sign up to set email alerts
|

Rutin in herbs and infusions: screening of new sources and consumption estimation

Abstract: Rutin has shown promising results in reducing various human diseases. However, many plants consumed in Brazil do not have their rutin content reported in the literature yet. More than eighty plants were analyzed using aqueous (popularly known as tea) and ethanolic extraction (employed in commercial rutin purification) by liquid chromatography. Rutin was found in 47 samples when ethanol extraction was used. Echinodorus grandiflorus had the highest content (14,878.7 mg 1000 g-1), followed by Sambucus nigra, Drim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…This protective effect has been attributed to antioxidant activity, which is one of the most studied mechanisms of action (Paśko et al, 2019). Several studies have shown that phenolic compounds (e.g., ferulic, caffeic, vanillic, and gallic acids) and flavonoids (e.g., rutin, quercetin, kaempferol, myricetin, and hesperidin) may be responsible for this protective effect (Hernández-Ledesma, 2019;Li et al, 2019;Khursheed et al, 2020;Meinhart et al, 2020). Given its healthy properties, the consumption of quinoa has been increasing; it is now used in cookies, pasta, soups, beverages, porridges, and other foods and drinks (Xu et al, 2020;Yadav, 2020;Zhang et al, 2019;Demir & Kılınç, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This protective effect has been attributed to antioxidant activity, which is one of the most studied mechanisms of action (Paśko et al, 2019). Several studies have shown that phenolic compounds (e.g., ferulic, caffeic, vanillic, and gallic acids) and flavonoids (e.g., rutin, quercetin, kaempferol, myricetin, and hesperidin) may be responsible for this protective effect (Hernández-Ledesma, 2019;Li et al, 2019;Khursheed et al, 2020;Meinhart et al, 2020). Given its healthy properties, the consumption of quinoa has been increasing; it is now used in cookies, pasta, soups, beverages, porridges, and other foods and drinks (Xu et al, 2020;Yadav, 2020;Zhang et al, 2019;Demir & Kılınç, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From a phytopharmaceutical technology point of view, the maceration process using an alcoholic solvent may lead to an enhanced extraction efficiency of both the phenolic acids and flavonoids, when compared to boiled water-based methods such as infusion and decoction (Llorent-Martínez et al, 2020;Meinhart et al, 2020). The higher yield of alcoholic extraction may be attributed to the intermediate eluotropic strength of methanol and ethanol (64.7 and 78.5, respectively) when compared to water ( 100), what therefore enhances the mass transfer of low molecular weight polyphenolic compounds (Stalikas, 2007) such as: caffeoylquinic acid derivatives; terpenes; glycoside flavonoids; and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Micheli, Sambucus nigra L., Drimys winteri J.R.Forst. or Taraxacum officinale Weber ex Wiggins (Meinhart et al, 2020) may deserve further attention for large-scale field experiments. If plants rich in rutin and ferulic were preferred, the activity of the extracts from sea buckthorn (Hippophae Rhamnoides L.) (Criste et al, 2020), Rhinacanthus nasutus (L.) Kurz (Huang et al, 2015), Artemisia absinthium L., Achil-lea millefolium L., Sambucus nigra L. or Salvia officinalis L. (Bljajić et al, 2021) could be explored.…”
Section: Opportunities For Future Gtds Treatmentsmentioning
confidence: 99%